Case Report: Guanfacine and methylphenidate improved chronic lower back pain in autosomal dominant polycystic kidney disease with comorbid attention deficit hyperactivity disorder and autism spectrum disorder - Kasahara, Satoshi; Kanda, Shoichiro; Takahashi, Miwako; Fujioka, Mao; Morita, Taito; Matsudaira, Ko; Sato, Naoko; Hattori, Motoshi; Momose, Toshimitsu; Niwa, Shin-Ichi; Uchida, Kanji (Frontiers in Pediatrics, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is an inherited renal disease characterized by the bilateral development of multiple cysts in the kidneys. Pain management is a clinically important issue, especially because approximately 60% of patients with ADPKD experience chronic pain related to hemorrhage from renal cysts, which significantly reduces their daily life. The cystic fibrosis transmembrane conductance regulator, the molecule responsible for cyst formation in ADPKD, is also the cause of cystic fibrosis. Since attention deficit hyperactivity disorder (ADHD) is known to occur frequently in conjunction with cystic fibrosis, ADPKD may be associated with ADHD. However, to our knowledge, no study has investigated 1) ADHD or autism spectrum disorder (ASD) as comorbidities with ADPKD, 2) the effects of ADHD medications on chronic pain in ADPKD, or 3) cerebral blood flow corresponding to guanfacine (GF) or methylphenidate (MP) treatment for chronic pain. We report the case of a 15-year-old girl with ADPKD, who had chronic back pain associated with ADPKD and had to withdraw from high school because the pain interfered with her daily life. Although she took antihypertensive medications to prevent bleeding, they did not provide adequate blood pressure control. The patient was referred to a child psychiatrist and diagnosed with ASD; however, the pain did not improve. Subsequently, she was referred to our pain center. The diagnosis of ADHD was confirmed and treatment with ADHD medications was initiated. Monotherapy with MP, atomoxetine, and GF resulted in hypertension and hypotension as side effects; however, a combination of MP 18 mg and GF 4 mg provided pain relief and moderate blood pressure control, and the patient was able to go on to college. During the course of treatment, there was an improvement in the distribution of cerebral blood flow in the prefrontal and insular cortices. Confirmation of an ADHD diagnosis comorbid with ASD enabled the use of ADHD medications. The combination of MP and GF improved chronic back pain and high blood pressure due to ADPKD and cerebral blood flow. Screening for ADHD is important in the treatment of ADPKD.